Penerapan Akuntansi Manajemen Lingkungan untuk Mendukung Pengambilan Keputusan Manajemen dalam Meningkatkan Eko-Efisiensi: (Studi Kasus Pada PT XYZ) - Putri, Yolanda; Novianty, Ira; Burhany, Dian Imanina; Nurmalina, Rina (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
Existing environmental problems require making appropriate management decisions while still paying attention to the efficiency of environmental costs incurred (eco-efficiency). The application of environmental management accounting assists management in making decisions to achieve eco-efficiency. This study aims to implement environmental management accounting as a basis for management decision-making related to cost efficiency and environmental management at PT XYZ.This type of research is qualitative research with a case study approach. The data presented are qualitative and quantitative with primary data sources obtained from interviews and observations and secondary data derived from documentation studies. The results of this study indicate that(1) PT XYZ has not implemented environmental management accounting as a whole (2) The eco-efficiency of companies will decrease in 2022 due to higher environmental costs than the previous year. (3) The application of environmental management accounting plays a role in supporting management decision making through information generated in physical and environmental cost reports.